2020
DOI: 10.1108/ijchm-06-2020-0594
|View full text |Cite
|
Sign up to set email alerts
|

The decision tree for longer-stay hotel guest: the relationship between hotel booking determinants and geographical distance

Abstract: Purpose Using the decision tree model, this study aims to understand the online travelers booking behaviors on Expedia.com, by examining influential determinants of online hotel booking, especially for longer-stay travelers. The geographical distance is also considered in understanding the booking behaviors trisecting travel destinations (i.e. Americas, Europe and Asia). Design/methodology/approach The data were obtained from American Statistical Association DataFest and Expedia.com. Based on the US traveler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Recently, a previous study found that LoS influences a consumer’s destination planning by positively influencing revisit intention (Wang et al , 2018), which is an important strategic issue for tourist destinations. In this light, existing literature investigating LoS mainly viewed the construct as a dependent variable and tried to identify determining factors and situational constraints to predict a tourist’s decision-making of LoS (Lee and Kim, 2021). Therefore, studies examining the impact of different LoS on consumers’ post-purchase behaviors are limited (Wang et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a previous study found that LoS influences a consumer’s destination planning by positively influencing revisit intention (Wang et al , 2018), which is an important strategic issue for tourist destinations. In this light, existing literature investigating LoS mainly viewed the construct as a dependent variable and tried to identify determining factors and situational constraints to predict a tourist’s decision-making of LoS (Lee and Kim, 2021). Therefore, studies examining the impact of different LoS on consumers’ post-purchase behaviors are limited (Wang et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The most recent research has used more sophisticated theoretical and methodological approaches, beyond the typical reliance on survey data and linear choice models, to understand the complex, nonlinear dynamics of hotel choice. For example, using machine learning and a decision tree model, Lee and Kim (2021) examined online travelers’ booking behavior on Expedia.com considering geographical distance between origin and destination. Wang et al (2020) proposed a picture fuzzy the interactive multi-criteria decision making (TODIM) method based on bounded rationality behavioral decision-making to identify differences in preferences among five traveler types.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The LoS has been suggested to potentially affect how a consumer makes a decision (Mariani et al , 2019). However, few prior studies have tried to examine this issue (Kim and Han, 2022; Lee and Kim, 2021). The LoS has primarily been studied as an outcome variable in the extant literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The LoS has primarily been studied as an outcome variable in the extant literature. In line with this, the literature has attempted to identify determinants and situational constraints in tourists’ decision-making regarding LoS at a hotel (Lee and Kim, 2021). Only a few studies have examined how LoS influences post-purchase behaviors (Kim and Han, 2022; Wang et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation